Educational intervention to improve effectiveness in treatment and control of patients with high cardiovascular risk in low-resource settings in Argentina: study protocol of a cluster randomised controlled trial. Issue 1 (31st January 2017) - Gulayin, Pablo; Irazola, Vilma; Lozada, Alfredo; Chaparro, Martin; Santero, Marilina; Gutierrez, Laura; Poggio, Rosana; Beratarrechea, Andrea; Rubinstein, Adolfo
Abstract : Introduction: Hypercholesterolaemia is estimated to cause 2.6 million deaths annually and one-third of the cases of ischaemic heart disease. In Argentina, the prevalence of hypercholesterolaemia increased between 2005 and 2013 from 27.9% to 29.8%. Only one out of four subjects with a self-reported diagnosis of coronary heart disease is taking statins. Since 2014, statins (simvastatin 20 mg) are part of the package of drugs provided free-of-charge for patients according to cardiovascular disease (CVD) risk stratification. The goal of this study is to test whether a complex intervention targeting physicians and pharmacist assistants improves treatment and control of hypercholesterolaemia among patients with moderate-to-high cardiovascular risk in Argentina. Methods and analysis: This is a cluster trial of 350 patients from 10 public primary care centres in Argentina to be randomised to either the intervention or usual care. The study is designed to have 90% statistical power to detect a 0.7 mmol/L reduction in low-density lipoproteins cholesterol from baseline to 12 months. The physician education programme consists of a 2-day initial intensive training and certification workshop followed by educational outreach visits (EOVs) conducted at 3, 6 and 9 months from the outset of the study. An on-site training to pharmacist assistants during the first EOV is performed at each intervention clinic. In addition, two intervention support tools are used: an app installed in physician's smartphones to serve as a decision aid to improve prescription of statins according to patient's CVD risk and a web-based platform tailored to send individualised SMS messages to patients. Ethics and dissemination: Ethical approval was obtained from an independent ethics committee. Results of this study will be presented to the Ministry of Health of Argentina for potential dissemination and scale-up of the intervention programme to the entire national public primary care network in Argentina. Trial registration number: NCT02380911 .